1980
DOI: 10.1007/bf00874662
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind study of prophylactic methenamine hippurate treatment of patients with indwelling catheters

Abstract: Catheterized patients with heavy bacteriuria and short catheter life received a short-course of antimicrobial therapy and then were allocated at random to double-blind treatment for 5 months with methenamine hippurate (MH), 1 g three times daily, or placebo 1 g 3 times daily. MH treatment reduced the number of catheter blockages and instances of spontaneous removal of the catheter, and doubled catheter life (p less than 0.001). It is suggested that the doubled catheter life was due to the reduced bacteriuria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The use of indwelling catheters in the management of aged patients with urinary' incontinence is associated with a non-controllable nosocomial situation [7,15,16]. It is suggested that catheters be replaced by diapers whenever possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of indwelling catheters in the management of aged patients with urinary' incontinence is associated with a non-controllable nosocomial situation [7,15,16]. It is suggested that catheters be replaced by diapers whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…First, antibiotics were re placed by methenamine hippurate, which has no ecological side effects. The function time of silicone-coated latex catheters was dou bled during treatment with methenamine hippurate but bacteriuria and pyuria per sisted [15,16], Then an attempt was made to make latex catheters bactericidal by coating with copper metal; the attempt has, however, not been a clinical success hitherto [17],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, chemotherapeutic agents were used against catheter-induced bacteriuria, but these had only a transient effect on catheter-induced bacteriuria (1, 2, 3). In addition, the patient's endogenous bacterical flora was profoundly disturbed, with selection of multiresistant opportunistic strains of bacteria (1,2,3).…”
mentioning
confidence: 99%